Revisiting run-up velocity in gymnastics vaulting - Fujihara, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The vault run-up velocity is important from a competitive aspect In gymnastics. Its importance is well understood by practitioners, and its measurement would seem to be simple. Relevant data are relatively abundant but disorganised in the literature. The purpose of this study was to delve into run-up velocity measurements in previous research and to interpret the data and the possible influences based on the methodologies of the studies. By organising a cluster of run-up velocity data as well as the methodologies of the previous studies, we have clarified what is known about run-up velocity and problems to be overcome for its practical use. This is one of the most essential steps to reaching ISBS's goal: to bridge the gap between researchers and practitioners.